INTERNATIONAL CONCEPT SYSTEM AS A STRATEGIC WAY OF MODERN SCIENCE DEVELOPMENT - Tsaryk, Olga; Sokol, Mariana; Wychruszcz, Anatoliy (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article outlines the determination of international system of pedagogical concepts in modern scientific society. The definitions of the major international terms have been explored. The purpose of the research is to define is to outline international concept system as a strategic way of modern science development. It was researched that international conceptual-categorical apparatus of pedagogical science is not only a thesaurus of concepts covering all the terms with their scientific interpretations used in the study, but also a set of interrelated concepts, which reflect the key content and functional aspects of the offered theory. The most frequently used international concepts of pedagogical science have been explained and determined in the article. Original definitions of international concepts have been offered by the authors in a summary table. The system level of scientific concepts that reflects the development degree of its theory and reveals the relationship of objects and the diversity of cognitive situations which arise during the study, education of person and allows the participant clearly outline the subject of research and build its consistent concept have been investigated during the study. It has been summed up that the operation of international concepts is a prerequisite for the study and construction of theoretical models, as well as for the study of educational processes in dynamics and prospects. It has been concluded that strict understandable system of concepts creates a conceptual-categorical apparatus of pedagogical science.